Better later than never: Post-response error monitoring in semantic illusions - Soares, S.; Jerónimo, R.; Ana Raposo (13º Encontro Nacional da Associação Portuguesa de Psicologia Experimental, 2018)
When deciding if sentences like “It was two animals of each kind that Moses took in the ark” are true most people answer affirmatively, despite holding correct knowledge. These semantic illusions (SI; Erickson & Mattson, 1981) demonstrate that cognitive control processes do not always prevent wrong answers. We investigated post-response monitoring processes, indexed by the error-related-negativity (ERN) ERP potential. Responses to SI were slower and less accurate, relative to false and true sentences. Crucially, the ERN for undetected SI was larger than the correspondent ERP potential (correct-response-negativity/CRN) found for correct responses to any type of sentence. These results demonstrate that monitoring processes may unfold even after an error is committed.